The Influence of Seed Biopriming with Rhizobacteria on The Control of Black Rot Disease by Xanthomonas campestris Pathogens - Rahman, Fakih Nur; Aini, Luqman Qurata; Syib`li, Muhammad Akhid (Research Journal of Life Science, 2023)
The use of chemical pesticides in agriculture has negative impacts on the environment and health and leads to pathogen resistance. As an alternative, microorganisms such as PGPR or PGPF can enhance plant resilience and growth. Biopriming can trigger systemic resistance, improve nutrient uptake, and protect plants from pathogen infection. This study aims to evaluate the potential of biopriming and the effects of rhizobacterial application on plants. There are three main tests: the pathogenicity test of Xanthomonas campestris, the rhizobacterial test on cabbage seeds and seedlings, and the effectiveness of rhizobacteria in suppressing black rot disease in cabbage. Rhizobacterial application increased peroxidase enzyme and total phenol levels in plants, as well as plant height and leaf number. Rhizobacteria also improved cabbage seed germination and suppressed plant diseases. In conclusion, all tested rhizobacteria induced resistance in cabbage plants by increasing peroxidase enzyme and total phenol levels. Rhizobacterium TO9 (Clostridium sp.) was the most effective in enhancing plant resistance. Rhizobacteria also stimulated cabbage growth. Further research is needed to understand the mechanisms and effectiveness of rhizobacteria under different agricultural conditions.